Direct atomic insight into the role of dopants in phase-change materials - Min Zhu (Nature Portfolio, 2019)
Quantitative imaging on the doping in phase-change materials for data storage remains scarce. Here, the authors combine electron microscopy, atom probe tomography, and simulations to determine the role of indium and silver dopants during recrystallization.